Aftermath [large type] - Blackstock, Terri, 1957- (Thorndike Press large print Christian fiction., 2021)
When police stop Dustin Webb with a warrant to search his trunk, he knows there must be a mistake. But he's horrified when the officers find explosives, and he can't fathom how they got there. Criminal attorney Jamie Powell was Dustin's best friend growing up. They haven't spoken since he left for basic training, but she's the first person he thinks of when he's arrested. Jamie knows she's putting her career on the line by defending an accused terrorist, but she'd never abandon him. Someone is framing Dustin to take the fall for shocking acts of violence -- but why?